PENGARUH DIAMETER PIPA DAN LUBANG BAKAR PADA TUNGKU PEMBAKARAN TEMPURUNG KELAPA DENGAN METODE PIROLISIS - Willy Alexander; Seprianto, Dicky; Martomi, Eka Satria (MACHINERY Jurnal Teknologi Terapan, 2022)
Coconut shell charcoal is a product obtained from imperfect combustion of coconut shells causing complex carbon compounds not to oxidize into carbon dioxide. This event is pyrolysis. This study aims to determine the influence of pipe diameter parameters and burn hole diameter on water content and ash content of coconut shell charcoal which test specimens are made using pyrolysis method combustion furnace. The test result data was analyzed using ANOVA with 2 FI full factorial design, using 2 factors and 2 responses modeled by Design-Expert (Trial) software. The results of the analysis revealed that the main factor that most influenced the moisture content and ash content of the test specimen was the pipe diameter factor. The contribution of the influence of pipe diameter on water content is 47% and the contribution of pipe diameter influence to ash content of 56%.